9 - Approches participatives et gestion décentralisée de la Forêt du Samori dans la Commune de Baye, Région de Mopti (Mali) - Kassibo, Bréhima (Africa Development, 2021)
Local participation is generally regarded as a prerequisite for effective natural resource management. This paper is based on the management of the Samori Forest, located in the Baye Council, in Mali, where several institutional arrangements bring together multiple actors (the state, decentralized bodies, and civil society. The article examines a nearly promulgated environmental decentralization reform. Indeed, the new law on the constitution of local communities, as well as two laws on forest management introduced by the Third Republic, recommends that the state should transfer powers and responsibilities to local authorities and individuals on public issues. These laws make a participatory approach one of the key principles of decentralized management of natural resources, favoring the participation of empowered local actors in decision-making. The failure to put these laws into effect has resulted in the exclusion of representatives of local democratic institutions in the administrative process and invalidates the participatory tool introduced by the NGO SOS Sahel, which has been concerned with the implementation of community-based forest resource management on the basis of a re- launch of traditional forest management associations.